Digestible threonine to lysine ratio in diets for laying hens aged 24-40 weeks - Rocha,Tatiana Cristina da (2013)
Two-hundred sixteen white laying hens were used to assess the ideal ratio of digestible threonine:lysine in diets for laying hens at 24 to 40 weeks of age. Birds were assigned to a randomized block design, with six treatments, six replicates per treatment and six birds per experimental unit. The cage was used as the blocking criterion. Experimental diets contained different digestible threonine:digestible lysine ratios (65, 70, 75, 80, 85 and 90%) with 142 g/kg of crude protein. Experimental diets were formulated to be isonitrogenous and isocaloric with different contents of L-glutamic acid. Feed intake (g/hen/d), egg production (%), egg weight (g), egg mass (g/hen/d), feed conversion ratio (kg/dozen and kg/kg egg), eggshell weight (g), albumen weight (g), yolk weight (g) and body weight gain (g) were assessed. The maximum egg production was observed at 78% digestible threonine:digestible lysine ratio, while the best values of feed conversion ratio (kg/dozen egg) and feed conversion ratio (kg/kg of egg) were observed at 77.6% and 75%, respectively. Feed intake, egg mass and egg contents (yolk, albumen and eggshell) were not affected by treatments. The estimated digestible threonine:digestible lysine ratio of Hy-Line W36 laying hens at 24 to 40 weeks of age is 78%, corresponding to 5.70 g/kg of dietary digestible threonine.